RESEARCH ON LANGUAGE PLANNING AND POLICY PROPOSAL OF A CHOSEN EDUCATIONAL SCHOOL - Akhmadjonov, Avazbek (Innovative Development in Educational Activities, 2023)
this paper is based on a proposal of language planning and policy on how to improve students’ speaking skills and what steps are recommended to take to achieve the targeted results. In this research work the educational setting and the teaching methods are analyzed with proposed plan to develop speaking skills of a chosen regional school.